OTIMIZAÇÃO DE ATIVIDADES LABORATORIAIS PELA APLICAÇÃO DE FERRAMENTAS DE PENSAMENTO ENXUTO (LEAN THINKING) - Rodrigues, Henrique Horácio (2021)
It is presented how some lean thinking tools can help to improve the routine of laboratory activities. Some problems such as lack of organization of time, records, materials, activities, among others, directly affect the quality of the service performed, given the complexity of laboratory tasks. The objective of this research is to propose actions to optimize laboratory activities through the application of lean thinking tools in a materials laboratory. For this, a survey of the most significant activities carried out in a testing laboratory on construction materials was carried out, via documentary research. Soon after, through observation, the problematic points in the processes were raised, so that optimization adjustments could be proposed, using lean thinking tools. Subsequently, the adjustments were validated by a focus group among laboratory technicians. Improvements achieved, such as the increase in the number of rehearsal rooms, organization of environments, reduction of displacement and effort and creation of a system for scheduling activities, contributed to a better work environment and better management of the public sector, it also collaborated with scientific production on lean thinking in a different area of the manufacturing sector. This research applied different lean thinking techniques, unlike most of the researches observed so far, which are dedicated to applying only one lean technique in laboratories. As a technical/technological product, the research generated an intervention report to optimize activities in experimental laboratories.